Chloroacetamide-Linked Nucleotides and DNA for Cross-Linking with Peptides and Proteins - Olszewska, Agata; Pohl, Radek; Brázdová, Marie; Fojta, Miroslav; Hocek, Michal (Bioconjugate chemistry, 2016)
Nucleotides, 2'-deoxyribonucleoside triphosphates (dNTPs), and DNA probes bearing reactive chloroacetamido group linked to nucleobase (cytosine or 7-deazadaenine) through a propargyl tether were prepared and tested in cross-linking with cysteine- or histidine-containing peptides and proteins. The chloroacetamide-modifed dNTPs proved to be good substrates for DNA polymerases in the enzymatic synthesis of modified DNA probes. Modified nucleotides and DNA reacted efficiently with cysteine and cysteine-containing peptides, whereas the reaction with histidine was sluggish and low yielding. The modified DNA efficiently cross-linked with p53 protein through alkylation of cysteine and showed potential for cross-linking with histidine (in C277H mutant of p53).
Keywords: acetamidy; cystein; Histidine; nukleotidy; DNA; Nucleic Acid Conformation; transport elektronů; Acetamides; Proteins; konformace nukleové kyseliny; Models, Molecular; Nucleotides; peptidy; proteiny; Protein Conformation; molekulární modely; Cysteine; histidin; konformace proteinů; Peptides; Electron Transport